Rectal Bleeding in Infants: Diagnostic Work-up and Management - Quitadamo, Paolo; Isoldi, Sara; Mallardo, Saverio; Zenzeri, Letizia; Ceccanti, Silvia; Battagliere, Ilaria; Del Bene, Margherita; Di Nardo, Giovanni (Current Pediatric Reviews, 2024)
Lower gastrointestinal bleeding is an alarming symptom in pediatrics, especially in infancy. However, it is commonly secondary to benign and self-limiting conditions, such as anal fissures, infections, and allergies; more rarely it is caused by more serious disorders, such as necrotizing enterocolitis, very early onset inflammatory bowel diseases, and vascular malformations. The present review aims at summarizing the different clinical conditions presenting with rectal bleeding in infancy and provides an evidence-based diagnostic work-up for the clinical management of patients with this occurrence.
Keywords: vascular malformations